Work environment during the COVID-19 pandemic in Saudi Arabia - Rehab Aburas (SAGE Publishing, 2021)
Background: COVID-19 is affecting all spheres of life. As of 8 September 2020, there have been 321,595 confirmed cases of COVID-19 and 4,107 deaths in Saudi Arabia. The concerns regarding work from offices and contacting others is a global concern during this pandemic. Most of workers are mainly concerns about getting infected and spread it to their families. Therefore, to cope with the COVID-19 pandemic, architects, urban planners, and designers have already switched their attention to visualizing the post-pandemic era; however, there are inadequate studies on how the antivirus-built environment will look. Accordingly, this study aims to reflect on perceptions of the work environment during the COVID-19 pandemic in Saudi Arabia. Design and Methods: An online questionnaire consisting of five questions was designed to collect the data and was distributed via SurveyMonkey in August 2020. Research ethics approval was sought from the institutional review board. A total of 87 respondents participated in this study. Results: The result shows that 57.83% of respondents were female and 42.17% were male. The majority of the respondents were from the public sector (49.40% - public sector, 43.37% - private sector, and 7.23% - other sectors). Overall, female participants were more concerned about work environments during the pandemic. Most of the participants were working in individual offices. Conclusion: The virus does not discriminate by gender. In order to respond effectively to the crisis, we need a whole-society approach to understand its differential impact on women and men. The findings will encourage policymakers and business owners to respond to the areas highlighted in this study as causing concern such as elevators, restrooms, and common areas.